2016
DOI: 10.53911/jae.2016.1103
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and accumulation of lead by fenugreek

Abstract: In the present study, the response of fenugreek (Trigonella foenumgraceum L.) along with remediation potential was tested against lead (Pb). A pot trial was set up in order to evaluate remediation efficiency of T. foenumgraceum. Growth parameters and remediation potential of fenugreek against different concentrations of Pb was compared. Different physical parameters were studied. Biochemical parameters like chlorophyll content, soluble protein, total soluble sugar and proline were analyzed. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Similar observations were recorded by Xalxo and Keshavkant [ 10 ] who clarified that fenugreek treated with 1200 mg L −1 of lead was able to accumulate Pb in roots more than shoots. Furthermore, Kaur [ 12 ] reported that the Pb accumulation capacity of fenugreek cultivated with 800 mg L −1 of Pb during 30 days was more important in roots than shoots. A recent study revealed that fenugreek stressed by zinc (Zn) and aluminum (Al) had an important accumulation factor of these HMs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar observations were recorded by Xalxo and Keshavkant [ 10 ] who clarified that fenugreek treated with 1200 mg L −1 of lead was able to accumulate Pb in roots more than shoots. Furthermore, Kaur [ 12 ] reported that the Pb accumulation capacity of fenugreek cultivated with 800 mg L −1 of Pb during 30 days was more important in roots than shoots. A recent study revealed that fenugreek stressed by zinc (Zn) and aluminum (Al) had an important accumulation factor of these HMs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of metal accumulation in roots more than shoots can be interpreted in terms of the intervention of a chemiosmosis process across the membrane of intact root cells [ 24 ]. It could also be correlated with a low TF leading to a higher potential of phytostabilization of HMs in plant roots [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation